Effectiveness of Different Intranasal Corticosteroid Delivery Methods in the Management of Chronic Rhinosinusitis with Nasal Polyps: A Comparative Review of Sprays, High-volume Irrigations, Exhalation Delivery Systems and Steroid-Eluting Stents. - Kowalska, Zuzanna; Bulwa, Maciej; Filak, Małgorzata; Cetera-Szmajduch , Katarzyna; Byra, Anna; Kowalczyk, Marta; Frey, Jan; Białas, Alicja; Miazga, Krzysztof (Journal of Education, Health and Sport, 2026)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a common inflammatory condition of the nose and paranasal sinuses persisting for 12 weeks or more. It is associated with substantial symptom burden and reduced quality of life. While intranasal corticosteroids (INCS) continue to be the baseline of treatment, their clinical efficacy is often hindered by suboptimal delivery. In order to improve patients' quality of life and decrease topical corticosteroid usage, special attention is paid to the role of health education in both the prevention and therapy of the condition. Aim: This study aims to systematically compare the effectiveness and clinical outcomes of four major intranasal corticosteroid (INCS) delivery methods - conventional sprays, high-volume rinses, exhalation delivery systems, and steroid-eluting stents - in the management of CRSwNP. Material and methods of research: This study is a brief review of the available literature mainly in the PubMed database and a comparison of the effectiveness of different intranasal corticosteroid delivery methods, with a focus on their therapeutic approach. Particular focus is given to adapting delivery method to patient’s condition and medical history. Specifically, the review evaluates patient-relevant outcomes, including disease-specific quality of life, symptom control, polyp size reduction, and the need for surgical intervention. By addressing these objectives, this study seeks to provide clinicians with concise guide for selecting the most appropriate delivery method tailored to individual patient and clinical context. Results: Across RCTs and systematic reviews, all topical corticosteroid strategies outperform placebo. Methods that enhance sinonasal deposition (high-volume irrigations and EDS) demonstrate larger and more consistent effects on polyp size and patient-reported outcomes than conventional sprays, particularly in post-surgical anatomy.